Serious Games are a Serious Tool for Team Research - Michael D. Coovert; Jennifer Winner; Winston Bennett; David J. Howard (Serious Games Society, 2017)
Serious games are an attractive tool for education and training, but their utility is even broader. We argue serious games provide a unique opportunity for research as well, particularly in areas where multiple players (groups or teams) are involved. In our paper we provide background in several substantive areas. First, we outline major constructs and challenges found in team research. Secondly, we discuss serious games, providing an overview and description of their role in education, training, and research. Thirdly, we describe necessary characteristics for game engines utilized in team research, followed by a discussion of the value added by utilizing serious games. Our goal in this paper is to argue serious games are an effective tool with demonstrated reliability and validity and should be part of a research program for those engaged in team research. Both team researchers and those involved in serious game development can benefit from a mutual partnership which is research focused.